2020
DOI: 10.3390/pharmacy8030109
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Augmented Reality Technology to Enhance Learning in Pharmacy Education: A Pilot Study

Abstract: There is increasing use of augmented reality (AR) technology, which combines the virtual and real world, in the tertiary education sector. AR enables flexibility in student learning, since this technology may be used in the face to face setting and may also be accessed by students at any time outside of this setting. The purpose of this study was to develop an AR tool and investigate its effectiveness for learning about the medication naloxone using AR in a MagicBook; and determine student opinions on its acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“… 57 , 58 Virtual reality (VR), also known as augmented reality, is a type of CBS where simulation software is utilized to aid pharmacy students in learning specialized tasks or situations. 59 , 60 It combines multimedia elements, such as audio, graphics, and animation, with textual information. VR simulation software mimics reality by modeling a clinical setting, outpatient/community pharmacy, or how to deal with a virtual patient.…”
Section: Patients Simulation Implemented In Pharmacy Curriculummentioning
confidence: 99%
“… 57 , 58 Virtual reality (VR), also known as augmented reality, is a type of CBS where simulation software is utilized to aid pharmacy students in learning specialized tasks or situations. 59 , 60 It combines multimedia elements, such as audio, graphics, and animation, with textual information. VR simulation software mimics reality by modeling a clinical setting, outpatient/community pharmacy, or how to deal with a virtual patient.…”
Section: Patients Simulation Implemented In Pharmacy Curriculummentioning
confidence: 99%
“…(Izard et al, 2018;Cao and Cerfolio, 2019) Pilot studies suggested that AR was a useful tool to create engaging and easy to use learning experiences in pharmacy education. (Salem et al, 2020;Schneider et al, 2020) Pharmacy students showed improvement in drug knowledge after completing the AR exercise and reported high usability and acceptability of AR for learning. (Salem et al, 2020;Schneider et al, 2020) AR technology can engage students into an active learning environment, which has been proven to be more effective than passive learning.…”
Section: Introductionmentioning
confidence: 99%
“…(Salem et al, 2020;Schneider et al, 2020) Pharmacy students showed improvement in drug knowledge after completing the AR exercise and reported high usability and acceptability of AR for learning. (Salem et al, 2020;Schneider et al, 2020) AR technology can engage students into an active learning environment, which has been proven to be more effective than passive learning. (Ramnanan and Pound, 2017;Styers et al, 2018;Coyne et al, 2019) The technical capabilities of AR can support a learning-by-doing approach stressed by the constructivist learning principles.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Schneider, et al 2020 revealed that AR technology allows flexible and repeated access to the content at any time. It has also been suggested that using AR for learning enables students to have a more absorbing and engaging environment without the loss of real world experiences [ 9 ].…”
Section: Introductionmentioning
confidence: 99%